Adsorption of cefotaxim sodium on activated carbons of various origin - Lishai, Nastassia V.; Savitskaya, Tatyana A.; Tsyhankova, Nadzeia G.; Hrynshpan, Dzmitry D.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2020)
The adsorption of the cephalosporin antibiotic sodium cefotaxime (CEFOT) on two activated carbons in the temperature range 288–313 K was under study. Experimental charcoal AC obtained from hydrolysis lignin was established to be mesoporous. It demonstrates greater CEFOT adsorption activity than the commercially available charcoal OU-A made from wood and characterized by both micro- and mesoporous structure. The surface modification of both activated carbons by a water-soluble polyelectrolyte cellulose acetate sulfate in the form of sodium salt (Na-CAS) leads to an increase in specific adsorption. The multilayer model with saturation (MMS) was used for data analysis. As a result, the number of molecules on the adsorption center, the density of adsorption centers, the total number of formed layers and the energy characteristics of adsorbate – adsorbent interactions at the interface and adsorbate – adsorbate ones within the adsorption layer were estimated.
Keywords: adsorption; multilayer model with saturation; activated carbon; сefotaxime sodium